Effect of media composition and biophosphate LOF on alligator avocado seedling growth - Ahmad Zakqi Nabiul Rohman; Refa Firgiyanto; Edi Siswadi; Fandyka Yufriza Ali; Sinta Dwi Rahma (Agrovigor, 2026)
Avocado cultivation in Indonesia shows strong potential due to increasing national production. Vegetative propagation using grafting techniques is key method for improving plant quality. Following grafting, seedlings must be transplanted into a new planting medium that supports optimal growth. Planting media composed of topsoil, raw husks, and manure as along with the application of Liquid Organic Fertilizer (LOF) derived from goat biophosphate, are crucial for seedling development. This study investigated the effects of planting medium composition and goat biophosphate LOF concentration on the growth of grafted ‘Alligator’ avocado seedlings. The study was conducted at the Wire House of Jember State Polytechnic from August to October 2023 using two-factor Randomized Block Design (RBD). The factorcs were (1) planting medium composition (P1 = 2:1:1, P2 = 3:1:2, P3 = 2:1:2) and (2) LOF concentration (K1 = 2 ml/L, K2 = 4 ml/L, K3 = 5 ml/L). Data analysis using ANOVA and DMRT at 5% and 1% significance levels, respectively, showed that the planting medium significantly affected the number of leaves (P1 was the most effective). The concentration of LOF significantly affected stem diameter (K3 was the most effective), and the interaction between the two factors significantly influenced plant height and number of leaves at 12 weeks after planting.